'A threat to the social order': a 'problem frame' analysis of the Safe Schools Coalition Australia programme within print media. Issue 6 (2nd November 2022) - Rawlings, Victoria; Loveday, Jenna
ABSTRACT: This paper reports on print media coverage of the Safe Schools Coalition Australia (SSCA) in the two years until its federal review and loss of funding. Through applying Altheide's theories of the 'problem frame' in mass media, articles from the 13 national and capital cities papers were analysed to ascertain the dominant productions surrounding the SSCA, and how these framed gender and sexuality diversity within and outside schooling environments. Analyses illustrated that print media dominantly constructed the programme using three 'problem frames'. These relied on fear productions of the possible threat towards childhood innocence, heteronormativity, and cisnormativity. Depictions of threats to 'freedom of speech' also emerged. These findings produce new evidence that in this context, gender and sexuality diversity at school was overwhelmingly constructed as problematic. We argue that these constructions contributed to broader national discourses of gender and sexuality diversity as being dangerous or risky, especially for young people.